Investigating the Effects of Subjective Norms and Trialability on English Teachers` Attitude toward the Use of Technology - Somaye Davoodi; Leila Akbarpour; Ehsan Hadipour (Vision: Journal for Language and Foreign Language Learning, 2020)
Despite the availability of many technological resources in academic settings and their determinant effect in the improvement of teaching and learning, it seems that teachers rarely used them. The aim of the present study is to investigate the effect of psychological variables on teachers` attitudes regarding technology use.  In this research, most applicable models like the 'technology acceptance model', 'theory of reasoned action', and 'innovation diffusion theory' are used as the foundation for developing a conceptual framework. Variables such as 'perceived usefulness', 'perceived ease of use', 'trialability', 'subjective norms', and 'attitude' are recaptured from these models. The participants of the present research are high school English language teachers in Shiraz. The researcher uses stratified sampling to identify a representative sample from the population. The present study is administered by using five questionnaires to assess variables. The data are analyzed by means of path analysis. According to the obtained result, perceived ease of use is found to be affected by subjective norms and trialability, which in turn influenced the attitude of teachers toward using technology in their teachings. The results propose that the most influential factor on attitude is trialability (β= 0.38). On the other hand, perceived usefulness has a significant, influential effect on attitude. Subjective norms has an indirect but important effect on attitude.